“Time wasted by health professionals is time not invested in patients”: time management practice and associated factors among health professionals at public hospitals in Bahir Dar, Ethiopia: a multicenter mixed method study - Addis, Berihun Alemayehu; Gelaw, Yared Mulu; Eyowas, Fantu Abebe; Bogale, Tewodros Worku; Aynalem, Zewdu Bishaw; Guadie, Habtamu Alganeh (Frontiers in Public Health, 2023)
Background: Time management is of utmost importance in healthcare facilities since time squandered by health professionals is time not invested in patients, and this affects the quality of care given to patients. This study aimed to assess time management practice and factors affecting it among health professionals at public hospitals in Bahir Dar, Ethiopia.Methods: Institution-based cross-sectional study supplemented with a qualitative study was conducted from April 21 to May 20, 2022, among health professionals working in public hospitals in Bahir Dar, Ethiopia. A simple random sampling technique was used to select 416 study participants. A pretested self-administered questionnaire was used to collect quantitative data, and an interviewer guide was used to collect qualitative data to complement quantitative data.Purposive sampling was used in the qualitative study, and 12 in-depth interviews were carried out till saturation was reached. The quantitative data were entered into Epi Data version 4.0 and analyzed using SPSS 25.0 whereas the qualitative data were analyzed manually using thematic analysis. To identify the associated factors, bi-variable and multivariable logistic regression analyses were used. The degree of associations was interpreted using odds ratio and 95% confidence interval at < 0.05 p-value.Results: Of 416 invited participants, 410 of them participated in the study yielding a 98.5% response rate. The magnitude of time management practice among health professionals was 66.1%